Tariffs Formation on oil transportation - Glyzina T. S. Tatiana Svyatoslavovna; Kolbysheva Yu. V. Yuliya Vladimirovna; Grivtsova I. S.; Dmitrieva N. V. (Petroleum Engineering Economics and Mining Law, 2016)
Title screen